Heat transfer and flow structures of supercritical n-decane in a regenerative cooling channel loaded with non-uniform heat flux - Liu, Jian; Xu, Mengyao; Ma, Kai; Liu, Chaoyang; Xi, Wenxiong (Frontiers in Energy Research, 2022)
Harsh and complex thermal environment in the combustor threatens safe-working of scramjets. In this study, heat Transfer and flow structures of supercritical n-decane under 3-MPa in regenerative cooling channel loaded with non-uniform heat flux distributions are investigated, including uniform, sinusoidal, increased and decreased heat flux distributions. A verified k-ω SST turbulence model is employed and corresponding mesh independence study is performed. From this work, the fluid temperature at the outlet of the heated channel is only determined by the averaged heat flux and all the regenerative cooling channels achieve the same temperature although loaded with different heat flux distributions. Compared with the fluid temperature, the wall temperature distribution is more sensitive to the variations of heat flux distribution. The regenerative cooling channels loaded with the sinusoidal heat flux distributions exists several high-temperature regions and the channel loaded with linear distributions changes the trend of temperature distribution. A larger temperature gradient is found in the regenerative cooling channel wall with a lower thermal conductivity. This work provides a good insight on the characteristics of flow and temperature field of regenerative cooling channels loaded with non-uniform heat flux considering effect of conjugate heat transfer.